Celiac Artery Thrombosis and Splenic Infarction as a Consequence of Mild COVID-19 Infection: Report of an Unusual Case - Arslan, Gokhan (Hämostaseologie, 2021)
COVID-19 has been associated with the hypercoagulable state in the literature. Patients who are admitted to the hospital with severe COVID-19 may have some thrombotic complications. These patients have a high risk for venous and arterial thrombosis of large and small vessels. Here, a 42-year-old female with celiac artery thrombosis and splenic infarction after a history of mild COVID-19 was presented.
Keywords: COVID-19; thrombosis; celiac artery thrombosis; splenic infarction